Pengaruh Pengaya Organik dan MikroOrganisme Lokal pada Pupuk Limbah Industri Tepung Aren Terhadap Pertumbuhan Tanaman Padi Ciherang (Oryza sativa, L.) - Sigit Muryanto (AGROTECH Research Journal, 2020)
The research entitled "The Effect of Organic Add-ons and Local Microorganisms on Fertilizer of Palm Sugar Flour Industry waste on growth of Ciherang Rice (Oryza Sativa, L.)" was held in Winong Village, Boyolali District, Central Java, Pebruary to June 2014. Rice is grown on polybags with regosol soil type, located at 70 30 'LS and 110050' BT, altitude 400-450 m above sea level, average air temperature 27 C, daily average Rh 76%, average rainfall 1000 mm/year. This research was under guidance of Prof. Dr. Ir. Supriyono, MS and Prof. Dr. Ir. Bambang Pujiasmanto, M.S. Agronomy Studies Program Graduate Sebelas Maret University, Surakarta. This study aims to determine the combination of treatment between organic and organic microorganisms optimal on the fertilizer of Aren Flour (LTA) for the growth of Rice Ciherang plant. The study used a Completely Randomized Block Design (RAKL) which was arranged factorially with two treatment factors. The use of MOL in Flour Sugar Flour consists of 3 levels of treatment, namely: M1: MOL Starbio; M2: MOL Fruit and M3: MOL Goat Rumen Addition of Ingredients on Palm Sugar Flour [LTA], consisting of 3 levels of treatment, namely: P1: LTA + Bekatul; P2: LTA + Cow Manure (Cow Dung) and P3: LTA + Goat Dung From the results of this study can be concluded that: MOL type has a significant effect on rice growth that is on the weight of stover and number of panicles. Organic add-ons have a very significant effect on the number of tillers, weight of stover and number of panicles. There was no significant interaction between MOL treatment and organic additives on Ciherang rice growth parameters. The most optimal treatment combination of Ciherang rice plant growth is M3P2 treatment [LAT + Goat Rumen + Cow Dung] and M3P3 [LAT + MOL Goat Rumen + PO Goat Dung].